The Synergy of the Corruption Eradication Commission and the Judicial Commission as an Effort to Improve the Justice System in Indonesia - Nur Rohim Yunus; Trini Diyani (UIN JAKARTA, 2021)
Judicial power is an autonomous authority charged with the responsibility of administering justice in order to uphold the rule of law and justice. It is self-contained and does not rely on other authorities to maintain public order. However, the judicial power will be harmed if the judge charged with enforcing the law and administering justice actually violates the law. This study employs a qualitative research method in conjunction with a literature review. The study's findings indicate that the Corruption Eradication Commission and the Judicial Commission continue to lack cooperation in supervising judges in court. Thus, the synergy between the Corruption Eradication Commission and the Judicial Commission is required to foster cooperation and coordination in the fight against corruption, enabling them to jointly uphold the honour, nobility, and proper conduct of judges effectively and efficiently in accordance with the law.